Thismia belumensis (Thismiaceae), a remarkable new species from The Royal Belum State Park, Gerik, Perak, Peninsular Malaysia - Siti-Munirah, Mat Yunoh (PhytoKeys, 2021)
This report describes Thismia belumensis Siti-Munirah & Suhaimi-Miloko, a novel species of achlorophyllous herb discovered in the Royal Belum State Park, Peninsular Malaysia. This new species is unlike any previously described species of Thismia. In particular, T. belumensis possesses a unique annulus, which has been expanded and modified into a cucullate (hood-like) structure. This structure covers the apical floral tube and has an opening on one side facing a thickened part of the annulus, and the off-centre floral aperture confers a zygomorphic symmetry to the flower, indicating T. belumensis is more similar to Thismia labiata J.J.Sm. This morphological detail makes this new species distinct from all other described species of Thismia. In this report, we provide descriptions, illustrations, colour plates, and the provisional conservation status of Thismia belumensis.